Effects of Oral Lipid‐Based nutritional supplements on appetite, energy intake, and lipid profile of moderately underweight children. Issue 2 (18th December 2022) - Zubair, Aqsa; Fatima, Sadia; Habib, Hamid; Nazli, Rubina; Shah, Inayat; Shah, Mohsin
Abstract: Oral lipid‐based nutritional supplements (LNS) are designed to ensure dietary adequacy and to improve malnourishment in children. Therefore, this study investigated the effects of 4 weeks of LNS on appetite, energy intake, and lipid profile of moderately underweight children (5–10 years old) with BMI‐Z score between −2 and − 3 SDS, recruited in a single‐blind randomized control trial. In addition to the regular dietary intake, fasting blood samples, anthropometric measurements, energy intake, and appetite responses were obtained before and after 4 weeks of LNS (535 kcal) or PLACEBO (92 kcal). After 4 weeks of supplementation mean energy intake (kcal) ( p  < .001), body weight (kg) ( p  < .001), BMI (kg/m 2 ) ( p  < .01), mid‐upper arm circumference (cm) ( p  < .01), total cholesterol (mg/dl) ( p  < .01) and fasting glucose (mg/dl) ( p  < .01) were raised significantly in the LNS group as compared to the PLACEBO group. No significant changes were detected in appetite responses (p > 0.05). In conclusion, LNS increases the overall energy intake, but does not affect the appetite but may induce hyperglycemia and hyperlipidemia. Abstract : This trial report the effects of lipid‐based nutritional supplements (LNS) on moderate underweight school going children. The recruited children (both girls and boys) with mean age 7.1 ± 1.5 years had a BMI‐Z score between ‐2 and ‐3 SDS. We found a significant increase in weight, BMI, mid upper arm circumference, energy intake, total cholesterol and fasting glucose in LNS group. Data from this study can be used in future programming of LNS for improvement of malnourished status in children.